1999
DOI: 10.1093/ptj/79.8.749
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Thirty Minutes of Light-Intensity, Intermittent Exercise on Patients With Chronic Fatigue Syndrome

Abstract: Background and Purpose. Currently, there is no consensus on exercise prescription for patients with chronic fatigue syndrome (CFS). This investigation examined whether light-intensity, intermittent physical activity exacerbated symptoms in patients with CFS immediately following exercise to 7 days following exercise. Subjects. Subjects were 9 women (mean ageϭ44.2 years, SDϭ8.4, rangeϭ29-56; mean weightϭ74.2 kg, SDϭ18.8, rangeϭ56.36-110.91; and mean heightϭ1.63 m, SDϭ0.8, rangeϭ1.55-1.78) and 1 man (ageϭ48 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…If postexertional malaise is caused by insufficient activation of the pain inhibitory systems during exercise, further research into the possible contributing factors is required. Indeed, it has been reported that ME/CFS patients are able to perform light to moderate exercise (40% of peak oxygen capacity) without exacerbating their symptoms [11–13]. If the exacerbation of symptoms following physical exertion is related to the intensity and duration of attempted activities, it would be valuable to examine different types of exercise.…”
Section: Introductionmentioning
confidence: 99%
“…If postexertional malaise is caused by insufficient activation of the pain inhibitory systems during exercise, further research into the possible contributing factors is required. Indeed, it has been reported that ME/CFS patients are able to perform light to moderate exercise (40% of peak oxygen capacity) without exacerbating their symptoms [11–13]. If the exacerbation of symptoms following physical exertion is related to the intensity and duration of attempted activities, it would be valuable to examine different types of exercise.…”
Section: Introductionmentioning
confidence: 99%
“…However it should be considered that the high frequency of pain in persons with CFS may be due, in part, to the inclusion of myalgias and arthralgias as two of the minor symptoms in the diagnostic criteria following the CDC (Fukuda et al, 1994). Besides the persistent musculoskeletal pain, CFS patients typically experience an exacerbation of their symptoms, after previously well‐tolerated levels of exercise (Fukuda et al, 1994; Clapp et al, 1999). They experience muscle pain after a level of exertion that does not cause any tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…The behavioural component encourages planned and supervised resumption of appropriate physical and mental tasks. A physical activity program is individually designed to take account of the patient's current level of disability 467 , 468 . After a prolonged period of illness and inactivity, new activities are introduced gradually and, most importantly, are “paced” (ie, scheduled to stop before they produce a significant exacerbation of symptoms).…”
Section: : Managing Patients With Cfsmentioning
confidence: 99%